2015
DOI: 10.1002/2014tc003787
|View full text |Cite
|
Sign up to set email alerts
|

What was the Paleogene latitude of the Lhasa terrane? A reassessment of the geochronology and paleomagnetism of Linzizong volcanic rocks (Linzhou basin, Tibet)

Abstract: The Paleogene latitude of the Lhasa terrane (southern Tibet) can constrain the age of the onset of the India-Asia collision. Estimates for this latitude, however, vary from 5°N to 30°N, and thus, here, we reassess the geochronology and paleomagnetism of Paleogene volcanic rocks from the Linzizong Group in the Linzhou basin. The lower and upper parts of the section previously yielded particularly conflicting ages and paleolatitudes. We report consistent 40 Ar/ 39Ar and U-Pb zircon dates of~52 Ma for the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
77
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 167 publications
(311 reference statements)
7
77
2
Order By: Relevance
“…Various studies found significantly different paleolatitude values: e.g., 10.0°± 5.3°N [Chen et al, 2010], 15.2°± 5.8°N [Liebke et al, 2010], 21.7°± 5.0°N [Dupont-Nivet et al, 2010], and 20°± 4°N [Huang et al, 2015]. Various studies found significantly different paleolatitude values: e.g., 10.0°± 5.3°N [Chen et al, 2010], 15.2°± 5.8°N [Liebke et al, 2010], 21.7°± 5.0°N [Dupont-Nivet et al, 2010], and 20°± 4°N [Huang et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies found significantly different paleolatitude values: e.g., 10.0°± 5.3°N [Chen et al, 2010], 15.2°± 5.8°N [Liebke et al, 2010], 21.7°± 5.0°N [Dupont-Nivet et al, 2010], and 20°± 4°N [Huang et al, 2015]. Various studies found significantly different paleolatitude values: e.g., 10.0°± 5.3°N [Chen et al, 2010], 15.2°± 5.8°N [Liebke et al, 2010], 21.7°± 5.0°N [Dupont-Nivet et al, 2010], and 20°± 4°N [Huang et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…We assume that 25 ± 10 °C reflects a reasonable temperature uncertainty for lacustrine carbonate precipitation that could account for the overall warmer Eocene conditions and low latitude46, even at moderate to high paleoelevations. We then used the mean δ 18 O c (VPDB) of lacustrine micrites of −5.1 ± 1.1‰ (1σ) and the temperature-dependent fraction equation between water and calcite47 to calculate the δ 18 O psw (psw - paleo-surface water) relative to SMOW - Standard Mean Ocean Water of −2.8 ± 1.7‰.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, Lippert et al () reevaluated available paleomagnetic data using a statistically rigorous filtering criteria and concluded that the LT was located at high tropical/low subtropical latitudes (e.g., ~20°N) since early Cretaceous. Later paleomagnetic investigations further supported this conclusion (e.g., Ma et al, ; Huang, Dupont‐Nivet, Lippert, Hinsbergen, Dekkers, Guo, et al, ; Huang, Dupont‐Nivet, Lippert, Hinsbergen, Dekkers, Waldrip, et al, ; Yang, Ma, Zhang, et al, ). The precollisional paleolatitude of the LT dated the TH‐LT collision to ~55–50 Ma and suggests that less than 1/3 of Cenozoic convergence is partitioned into Asian lithosphere (Lippert et al, ; van Hinsbergen et al, ).…”
Section: Introductionmentioning
confidence: 89%
“…Notably, these Linzizong volcanic rocks were restudied by Huang, Dupont‐Nivet, Lippert, Hinsbergen, Dekkers, Guo, et al () and Huang, Dupont‐Nivet, Lippert, Hinsbergen, Dekkers, Waldrip, et al () with further rock‐magnetic analyses and petrographic observations, revealing that the lower units have been remagnetized. In addition, Huang, Dupont‐Nivet, Lippert, Hinsbergen, Dekkers, Guo, et al () and Huang, Dupont‐Nivet, Lippert, Hinsbergen, Dekkers, Waldrip, et al () argue that a quick latitudinal movement of the LT at this time interval is neither observed by paleopoles from the LT since Cretaceous (e.g., Lippert et al, ; Ma et al, ; Sun et al, ; van Hinsbergen et al, ; Yang, Ma, Zhang, et al, ) nor predicted by the apparent polar wander path of Eurasia or East Asia since Cretaceous (Cogné et al, ; Torsvik & Cocks, ; Torsvik et al, , ). Also, it is not supported by geological observations and reconstructions (e.g., Yin & Harrison, ; Johnson, ; van Hinsbergen, Kapp, et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation